DAMPAK PEMANENAN KAYU DENGAN TEKNIK REDUCED IMPACT LOGGING TERHADAP KERUSAKAN TEGAKAN SISA DI HUTAN ALAM - Muhdi (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2009)
This research examined the effect of Reduced Impact Logging (RIL) to residual stand damages in natural tropical forest, West Kalimantan. The effect of Reduced Impact Logging to residual stand were studied using the data of three plots with each size 100 m × 100 m are placed based on random at landing, middle skiddtrail and tips of skiddtrail, respectively. The objective of this research is to know the effect of reduced impact logging to residual stand damages in tropical forest. The results of the research showed that that the potency of commercial timber species in conventional timber harvesting and RIL were as follow 408 N/ha and 432 N/ha. The degree of residual stand damages based on tree population and stage of vegetation development in conventional timber harvesting and RIL was as follow: for seedlings 34.42% and 23.17%, for saplings 35.13% and 21.72%, for poles and trees 33.15% and 19.53%. Based on the size injury of every individual tree, the degree of the trees damages caused by timber harvesting in conventional timber harvesting and RIL was as follow: trees heavy injury 64.66% and 57.20%, trees medium injury 20.30% and 24.00%, and trees light injury 15.03% and 18.80%. The most type stand damage are the falling dawn 36.84% and 32.01% and broken trees 22.78% and 21.25%. These researches indicated that conventional timber harvesting in the tropical natural forest caused heavier damage on residual stand when compared with a Reduced Impact Logging.